John McHale, l’Amérique passée à la machine - Juliette Bessette (Les Cahiers de l'École du Louvre)
In 1956 the artist John McHale returned to London after spending a year at Yale University. From the United States, he brought back dozens of mass-market magazines whose pages were full of images of consumer goods and objects of popular culture. From this material, he produced several collages, twisting the iconographical sense of the fragments chosen by reusing them in new compositions. In the collage entitled Machine Made, America appeared an intriguing figure evoking a robot, with a very powerful “Pop” visual impact. Its symbolic value is grasped in a specific historical and cultural context, that of the United Kingdom in reconstruction during the post-war years.